Electrical and optical characterization of Bis(7-methoxybenzofuran-2-il) ketone - Da?delen, F.; Koca, M.; Kirilmiş, C.; Aydo?du, Y. (My University, 2007)
The electrical and optical properties of Bis(7-methoxybenzofuran-2-il) ketone have been experimentally characterized. The optical band gap of Bis(7-methoxybenzofuran-2-il)ketone was found as 2.76 eV. Single-oscillator energy and dispersion energy of the sample were calculated by plotting (n 2-l)-1-(hu)2 and found as 4.58 eV and 28 eV, respectively. The refractive index for long wavelength values (n ?) and the ratio of carrier concentration to the effective mass(N/m ) were obtained as 2.41 and 4.36 I048 g-1cm -3, respectively. © 2007 American Institute of Physics.
6TH International Conference of the Balkan Physical Union -- 22 August 2006 through 26 August 2007 -- Istanbul
Keywords: Optical properties; Reflectance; Single-oscillator energy